Dampak Konten Bertema Psikologi Dalam Media Sosial TikTok Terhadap Fenomena Self Diagnose Pada Generasi Z - Elisa Febriana; Ulfa Amalia (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
The rapid advancement of technology in the era of globalization has been accompanied by the emergence of various social media, one of which is TikTok social media. TikTok is a social platform focused on music videos that was first introduced in September 2016. Currently, 76% of TikTok users are dominated by generation Z. All types of video content on TikTok include psychology-themed content, which can lead to the phenomenon of self-diagnosis after viewing the content. The purpose of this study is to determine the impact of psychology-themed content in TikTok social media on generation Z. This research uses a qualitative descriptive approach method. The results of this study indicate that the phenomenon of self-diagnosis has an impact experienced by the subject, such as the subject experiencing interference in carrying out daily activities, the subject will search for additional information related to the symptoms experienced through digital media, the subject feels that his energy has decreased, the subject experiences a decrease in mood, and is easily emotional. In addition, in this study, researchers found that the phenomenon of self-diagnosis has a positive impact, namely the subject after doing self-diagnosis feels more empathetic with other individuals. The findings of this study are expected to not only enrich the academic literature, but can provide insight for generation Z to be more selective in choosing psychology-themed content, so as not to create a tendency to self-diagnose.